Smart traffıc controller based on traffıc densıty and prioritised emergency vehicle clearance. - Satheeskanth, N.; Mathushan, M.; Joy Mathavan, J.; Kunaraj, A.; Daisan, G. (Springer link, 2022)
Traffic lights play a key role in avoiding traffic congestion especially in cities in peak time. The traffic that built up in peak hours is the result of mismanagment of traffic in the off-peak hours is the bitter truth. In this paper, the application of the Ultrasonic sensors and micro controller prioritising the flow of traffic in the road based on vehicle density is widely discussed. The emergency vehicles are identified using RFID in the proposed prototype and given the top priority. Portable smart traffic management system is built as a prototype using inductive sensing elements, RF ID and Micro controller. The prototype of the smart traffic control system was built and tested in the controlled scenarios, comprehensive study was made and the results were thus obtained. The obtained results clearly shows that smart traffic controller is highly effective in clearing the traffic compared to the traditional traffic control system.
Keywords: Smart traffic controller; Traffic density; Micro controller; RFID